ROLE OF CYTOKINES IN GENERALIZED PARODONTITIS DURING PREGNANCY - T.A. Timokhina; O.V. Linovitska; V.A. Timokhina (Bogomolets National Medical University, 2016)
The aim - to study the changes of pro- and anti inflammatory cytokines in the saliva of pregnant women with generalized periodontitis in the dynamics of treatment.